Increased risk for alcohol- and other substance-exposed pregnancies among women who smoke tobacco: A secondary analysis of a primary care-based intervention - Thomas F. Northrup; Angela L. Stotts; Stephen M. Fischer; Kirk L. von Sternberg; Mary M. Velasquez (Tobacco Induced Diseases)
Introduction Among women at risk for alcohol-exposed pregnancies (AEP), smoking tobacco may be associated with increased severity of alcohol use, and risk for tobacco-exposed and other substance-exposed pregnancies (TEPs/SEPs). Our secondary data analysis of the ‘CHOICES Plus’ intervention trial explored AEP and SEP risk by smoking status.